Desenvolvimento de conversor bidirecional isolado para controle de carga e descarga de bancos de baterias - Silva, Edivan Laercio Carvalho da (2018)
The bidirectional and isolated converters discussed in this work are of great interest for applications such as UPS’s (Uninterrupted Power Supply) and hybrid generation power systems. They allow the charging and discharging of the batteries in a single equipment, which can present high voltage gain and provide galvanic insulation to the battery bank. In the development of this work, it is proposed the design and implementation of a converter with low levels of voltage and current ripple on both sides of the converter, besides the possibility to operate in the regulation of the DC link with fixed voltage value and to operate without the use of auxiliary circuits to ensure bidirectional operation. The study is based on the design, simulations and implementation of the converter, analyzing its behavior under different points of operation of the batteries. In order to control charge and discharge processes of the batteries, the converter was modeled from the state space model, allowing the design of the controllers involved in the system. In this sense, with the implementation of the converter in the laboratory, has as main contributions of the work modeling of the converter, implementation of the design of control for the charge of the batteries, regulation of the voltage in the DC link and the proposal of modulations that allow the converter to operate without the use of auxiliary circuits.